2015
DOI: 10.1007/s11011-015-9743-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical science workshop: targeting the gut-liver-brain axis

Abstract: A clinical science workshop was held at the ISHEN meeting in London on Friday 11th September 2014 with the aim of thrashing out how we might translate what we know about the central role of the gut-liver-brain axis into targets which we can use in the treatment of hepatic encephalopathy (HE). This review summarises the integral role that interorgan ammonia metabolism plays in the pathogenesis of HE with specific discussion of the roles that the small and large intestine, liver, brain, kidney and muscle assume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 117 publications
0
31
0
1
Order By: Relevance
“…Since the 1930s, ammonia has been known to play an important role in the pathophysiology of hepatic encephalopathy [4]. However, hyperammonemia can be The Neurobiology of Hepatic Encephalopathy DOI: http://dx.doi.org /10.5772/intechopen.86320 found in patients without hepatic encephalopathy, and normal levels of ammonia can be seen in patients with advanced hepatic encephalopathy [9]. Serum ammonia dosage is also not a good parameter for evaluating the severity of the disease [10].…”
Section: The Role Of Intestinal Microbiota and Enterocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1930s, ammonia has been known to play an important role in the pathophysiology of hepatic encephalopathy [4]. However, hyperammonemia can be The Neurobiology of Hepatic Encephalopathy DOI: http://dx.doi.org /10.5772/intechopen.86320 found in patients without hepatic encephalopathy, and normal levels of ammonia can be seen in patients with advanced hepatic encephalopathy [9]. Serum ammonia dosage is also not a good parameter for evaluating the severity of the disease [10].…”
Section: The Role Of Intestinal Microbiota and Enterocytesmentioning
confidence: 99%
“…In adults, approximately 1000 mmol (17 g) of ammonia is produced per day [12]. In cirrhotics, its serum concentration increases two to three times, an increase that is also exacerbated by the induction of glutaminase expression by enterocytes, which hydrolyzes the amino acid glutamine into glutamate and ammonia to obtain energy [9]. At least one haplotype of the glutaminase gene appears to be related to a higher propensity to develop clinically symptomatic encephalopathy, demonstrating that the constitutive activity of this enzyme undergoes genetic variations [13].…”
Section: The Role Of Intestinal Microbiota and Enterocytesmentioning
confidence: 99%
“…Multiple components have been implicated, including ammonia, inflammation, oxidative stress and altered composition of the gut microbiota . Hyperammonaemia and systemic inflammation have a central role in the pathogenesis of HE . Furthermore, an in vitro study found that reactive oxygen species (ROS) were produced when astrocytes were exposed to ammonia and inflammatory cytokines .…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, therapies have focused on reducing ammonia levels; however, systemic inflammation, as a cofactor, is also crucial in HE . Therefore, the ideal therapeutic strategy for HE includes medications that can reduce the blood ammonia level and systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The NADs are classified as osmotic laxatives but have also been classified as prebiotics , a generic term referring to agents that induce the growth or activity of commensal microorganisms. Although the pathogenesis of HE is incompletely understood, there is general agreement that the gut‐derived neurotoxin ammonia plays a key role . NADs reduce the intestinal production/absorption of ammonia through several potential mechanisms: (1) catharsis : the colonic metabolism of the NADs results in an increase in intraluminal gas formation and intraluminal osmolality and a reduction in intraluminal pH and transit time; (2) bacterial uptake of ammonia : the volatile fatty acids released during the colonic metabolism of NADs are used as a preferred substrate by the colonic bacteria with ammonia as the nitrogen source for protein synthesis; the increase in bacterial numbers additionally “bulks” the stool and contributes to the cathartic effect; (3) intestinal ammonia production : NADs inhibit glutaminase activity and interfere with the intestinal uptake of glutamine and its subsequent metabolism to ammonia; (4) gut microbiome: cirrhosis is associated with dysbiosis and changes in the colonic microbiome while additional changes in the microbiome may be observed in patients with HE; NADs can beneficially affect microbiota composition …”
mentioning
confidence: 99%